Estratégias de seleção dentro de progênies em duas populações de myracrodruon urundeuva Fr. All. - Guerra, Carla Renata Silva Baleroni [UNESP]; De Moraes, Mario Luiz Teixeira [UNESP]; Da Silva, Cristina Lacerda Soares Petrarolha [UNESP]; De Oliveira Canuto, Daniela Silvia [UNESP]; Da Costa Andrade, João Antonio [UNESP]; Freitas, Miguel Luiz Menezes; Sebbenn, E. Alexandre Magno (My University, 2009)
Myracrodruon urundeuva Fr. All. is a tree species threatened by human pressure. For this reason, this research aimed at evaluating the behavior of two populations of M. urundeuva in a heterogeneous plantation as a support for genetic ex situ conservation. Two progeny tests of M. urundeuva were evaluated. The tests were established in Selvíria, MS in 1992 as a heterogeneous plantation, composed of 25 families from Aramina, SP and 25 from Selviria, MS. The following silvicultural traits were evaluated: DBH (Diameter at breast height), DMC (average diameter of crown), height (ALT), stem form (FOR) and survival (SOB). The results based on the REML/BLUP method, suggest that populations of M. urundeuva from Aramina and Selviria have a good adaptation to environmental conditions of Selvíria. This became evident by the high survival rate. Genetic variation was higher in the Selvíria population when compared to the Aramina population. By using multi-effect index (IME), it is possible to select progenies that can provide a good selection gain and high variation. In that case, a maximum Kf must be established. This condition yields a higher genetic gain in the Selvíria than in the Aramina population.
Selection strategies within progenies of two Myracrodruon urundeuva Fr. All. Populations.
Keywords: Aroeira; Genetic parameter; Multi-effect index; Quantitative genetics; Average diameter; Diameter-at-breast heights; Environmental conditions; Ex situ; Genetic gain; Genetic variation; Multi-effect; Progeny tests; Stem form; Survival rate; Tree species; Chromosomes; Forestry; Astronium; Genetic Engineering